2014
DOI: 10.1016/j.applthermaleng.2013.10.052
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on RCCI combustion in a heavy duty diesel engine using in-cylinder blending of diesel and gasoline fuels

Abstract: ElsevierBenajes Calvo, JV.; Molina Alcaide, SA.; García Martínez, A.; Belarte Mañes, E.; Vanvolsem, M. (2014). An investigation on RCCI combustion in a heavy duty diesel engine using in-cylinder blending of diesel and gasoline fuels. Applied Thermal Engineering. 63 (1) AbstractAn experimental and numerical study has been carried out to understand mixing and auto-ignition processes in RCCI combustion conditions, using gasoline and diesel as low and high reactivity fuels, respectively. Three parametrical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(61 citation statements)
references
References 20 publications
2
53
0
6
Order By: Relevance
“…Kim et al [2] studied the effect of a two stage injection (earlier injection and late injection near top dead center) on combustion behavior and engine emissions. The results showed that the two-stage injection can reduce NOx emissions compared to single injection DI diesel engine when the injection timing of the first and main injections is optimized.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [2] studied the effect of a two stage injection (earlier injection and late injection near top dead center) on combustion behavior and engine emissions. The results showed that the two-stage injection can reduce NOx emissions compared to single injection DI diesel engine when the injection timing of the first and main injections is optimized.…”
Section: Introductionmentioning
confidence: 99%
“…It has a port injector for low reactive fuel (LRF) and a direct injector for high reactive fuel (HRF) [14,51,56,[62][63][64][65][66]. Figure 5 shows the experimental setup for RCCI with port and direct injection (Dual fuel).…”
Section: Rcci With a Port And A Direct Injection (Dual Fuel)mentioning
confidence: 99%
“…Gasoline has a high octane number (98) and Diesel has a high cetane number (52) [14,67]. Fuels with high octane number can bear high compression ratios [68].…”
Section: Gasoline/dieselmentioning
confidence: 99%
See 1 more Smart Citation
“…RCCI relies on substantial differences in the reactivity of the involved fuels. The most common combination in RCCI is diesel-gasoline [6,7] as these fuels are the primary fuels in the automotive industry. The previous research outlined that fuel composition is the most influential parameter of the combustion performance.…”
Section: Introductionmentioning
confidence: 99%